Recent English loanwords in Slovene - Šabec, Nada (ELOPE (Ljubljana), 2009)
The paper discusses Slovene-English language contact in general and English loanwords in Slovene in particular. The focus is on recent loanwords, where a great deal of variability in their pronunciation and spelling can be observed depending on the time of their borrowing, the channel of transmission (oral or written) and the degree of their linguistic and social integration into Slovene. Sociolinguistic variables such as the age and education of the users play a role as well, as do the differences between the phonological and orthographic systems of the two languages. In addition to phonological, morphological and orthographic aspects of English loanwords, their meaning and its occasional adaptations and modifications will be addressed. Data for illustration purposes will be taken primarily from the media, especially electronic ones (blogs, forums), since this is the field in which various forms of loanwords feature most frequently.
Keywords: angleščina; besedišče; English; izposojenke; jezikovni razvoj; jezikovni stik; language contact; language development; loanwords; Slovene; slovenščina; sposojenke; vocabulary